GROUNDED THEORY ABOUT THE USE OF LEARNING MANAGEMENT SYSTEM (LMS) TO DISTANCE EDUCATION MANAGEMENT - Oliveira, Paulo Cristiano de; Nakayama, Marina Keiko (Revista Gestão Organizacional, 2023)
Purpose: develop a substantive theory of factors influencing the use of Learning Management System in the management of Distance Education. Method / approach: the Grounded Theory guided the methodological procedures in the light of Strauss and Corbin (2008), and ATLAS.ti Software was used for data analysis. Mains findings: six factors were integrated around the central category, allowing the elaboration of the theory fundamental hypothesis and the establishment of causal and intervening conditions. The relational model, which consists of eight propositions, allowed the emergence of four consequences. The central category analysis revealed four sub processes, which involve its mechanisms of action/interaction. In addition, it was possible to identify external and internal contextual conditions that influence the mediation strategies in a sequence of four movements in three phases along time. Methodological / social / managerial contributions: the research responds to the general theories about the use of LMS from the perspective of managers. Also, can represent an advance in the sense of contributing with a systemic view of the LMS as an administrative-educational mediator element, recognizing components, dynamics, and movement. The study can assist in the development of technological and management solutions based on business Intelligence systems (BI), big data, and learning analytics systems aligned to the LMS to improve distance education management. Originality / relevance: the results will add up to this area research, showing implications of digital technologies use at distance education management process.